Individual-based versus Group-based Instructions in Classical Guitar Teaching at Indonesian Tertiary Arts Education - Andre Indrawan; Agnes Iklimah (Universitas Negeri Semarang, 2023)
Higher education policy implementation impacts more programs’ development of new music studies that cause the emergence of different classical guitar study curricula with their durations and credit weights varieties, which overlap each other. There has also been a new discourse on controversial group-based instruction strategies in instrumental training among teachers who have been using individual-based in running classical guitar courses. The aim of this research is to investigate the shifting discourse from individual to group instructions in classical guitar courses. This study uses a qualitative survey of several classical guitar teachers at four music departments in Indonesian art universities. In conclusion, almost all teachers apply individual instruction and it seems that they opposed the discourse of classical guitar group instruction. Although they also recognise the benefits of the group-based instruction model, up to date the students-teachers ratio for classical guitar studies is still between one to five students, so individual instruction is more reasonable to apply. This research offers the basic concept of developing a blended learning model that combines individual and classroom instruction strategies to anticipate the future growth of classical guitar student interest.